The Level of Alexithymia (Emotional Loss) and Emotional Representation and Its Relationship to Post-Traumatic Stress Disorder among Sample of Syrian Refugee Children in Karak Governorate - Faten Saleh Al-Khrasha (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
This study aimed to reveal the correlation between emotional representation and alexithymia (emotional loss) and their relationship to post-traumatic stress disorder in Karak Governorate, and to identify the level of alexithymia (emotional loss) in a sample of Syrian refugee children in Karak Governorate, and identify the level of emotional representation in a sample Children of Syrian refugees in Al-Karak Governorate, and to identify the level of post-traumatic stress disorder among the children of Syrian refugees in Al-Karak Governorate. The descriptive analytical-relational approach was used to achieve the objectives of the study. The study sample consisted of (200) male and female refugees from the children of Syrian refugees in Al-Karak governorate who were chosen by the available method. The level of emotional representation among the children of Syrian refugees was medium, and the results showed that the level of post-traumatic stress disorder among the children of Syrian refugees was moderate. At the level of significance (α≤0.05) between the emotional representation scale and the post-traumatic stress disorder scale, the study presented a set of recommendations, including conducting follow-up studies to track the level of post-traumatic stress disorder among Syrian refugees at different age groups.